Environmental Disclosure Quality and Financial Performance of Fast Food Chain Businesses in General Santos City - Morales, Janvel; Calunod, Dexter Joy; Libo-on, Laarni; Auditor, Michael; Obeso, Maria Cristina; Tomindug, Jibran (International Journal of Research in Interdisciplinary Studies, 2026)
This study explored the relationship between environmental disclosures quality and the financial performance of fast-food chain businesses in General Santos City. The present research study used a quantitative method, employing a descriptive correlational design to investigate the nature of the mentioned variables as well as the relationship between them. This study is anchored on the Stakeholder Theory of Freeman (1984) and Legitimacy Theory by Deegan (2002) and Suchman (1995). After gathering the mean rating of the 111 fast-food chain businesses, results showed a high level of hard environmental disclosure, soft environmental disclosure, and financial performance. Using the Pearson Product Correlation Coefficient, the researchers determined that there is a significant relationship between the environmental disclosure quality and the financial performance of Fast Food Chain Businesses in General Santos City. Ultimately, it is recommended that future research should pursue other types of enterprises or extend to different geographical areas.